Comparative Study of Selected Parameters of Gender Discrimination in Rural Versus Urban Population of Ahmedabad, Gujarat - Rashmi Sharma; S Mukherjee (Medsci Publications, 2011)
It was a population based cross sectional study done with the objective of comparing some parameters (attitude & practice) of gender discrimination (GD) in rural and urban areas of Ahmedabad district. A population of 963 (446 urban & 517 rural) showed alarmingly adverse sex ratio (SR) as low as 562 among urban preschoolers. GD was prevalent in both study areas but manifested differently. Preference of male child by both partners an indicator of gender discrimination was seen in both areas, It correlated with female literacy, their low mean age at marriage and first conception. While urban areas showed more adverse sex ratio coupled with awareness and use of Ultrasonography (USG) for sex determination and poor employment status, rural areas exhibited (along with adverse sex ratio) poor literacy and employment status of females and poor contraceptive use.